Non-sliding Fixation Shows Improved Clinical Outcomes for Displaced Femoral Neck Fractures as Compared to Sliding Fixation - Xu, Xiangyu; Lv, Yang; Cui, Zengzhen; Fan, Jixing; Zhou, Fang; Tian, Yun; Ji, Hongquan; Zhang, Zhishan; Guo, Yan; Yang, Zhongwei; Hou, Guojin (Frontiers in Surgery, 2022)
Objective: To compare the clinical outcomes between use of sliding fixation (three cannulated screws, TCS) and non-sliding fixation (four cannulated screws, FCS) in the treatment of femoral neck fractures. Methods: We retrospectively analyzed 102 patients with fresh femoral neck fractures treated with TCS (60 cases) and FCS (42 cases) between January, 2018 and December, 2019. The demographic data, follow-up time, hospitalization time, operation time, blood loss, length of femoral neck shortening (LFNS), soft tissue irritation of the thigh (STIT), Harris hip score, and complications (such as internal fixation failure, nonunion, and avascular necrosis of the femoral head) were also collected, recorded, and compared between the two groups. Results: A total of 102 patients with an average age of 60.9 (range, 18–86) years were analyzed. The median follow-up time was 25 (22 to 32) months. The LFNS in the FCS group (median 1.2 mm) was significantly lower than that in the TCS group (median 2.8 mm) (P<0.05). In the Garden classification, the number of displaced fractures in the TCS group was significantly lower than that in the FCS group (P<0.05). The median hospitalization time, operation time, blood loss, reduction quality, internal fixation failure rate (IFFR), STIT, and Harris hip score were not statistically different between the two groups (P>0.05). However, in the subgroup analysis of displaced fractures, the LFNS (median 1.2 mm), STIT (2/22, 13.6%), and Harris hip score (median 91.5) of the FCS group at the last follow-up were significantly better than the LFNS (median 5.7 mm), STIT (7/16, 43.8%), and Harris hip score (median 89) of the TCS group (P<0.05). No complications such as incision infection, deep infection, pulmonary embolism, or femoral head necrosis were found in either group. Conclusion: TCS and FCS are effective for treating femoral neck fractures. For non-displaced fractures, there was no significant difference in the clinical outcomes between the two groups. However, for displaced fractures, the LFNS of the FCS is significantly lower than that of the TCS, which may reduce the occurrence of STIT and improve the Harris hip score.